Distal interphalangeal Joint Arthrodesis using only Kirschner Wires in small distal Phalanges - Lee, Jun-Ku; Lee, Soonchul; Choi, SeongJu; Han, Dong Hun; Oh, Jongbeom; Kil, Minkyu; Han, Soo-Hong (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2021)
Purpose To report the clinical and radiographic results of arthrodesis of relatively small-sized distal interphalangeal joints (DIPJs) using only K-wire fixation.Patients and methods Between January 2000 and December 2018 28 arthrodesis in 21 patients (9 males and 12 females with an average age of 52.1 years) with relatively small-sized DIPJs were performed using only K-wires. Data on patient’s characteristics, such as age, sex, affected finger, and the number and size of the used k-wires were collected from the medical database. The narrowest diameter of the cortex and medulla of the distal phalanx was measured on preoperative plain radiographs. The time to union and the arthrodesis angle was determined using serial X-ray radiography follow-up. Preoperatively and at the latest follow-up examination, pain using the visual analogue scale (VAS) and the quick DASH score was registered. In addition, complications were investigated.Results Average follow-up period was 11.4 months. The small finger was mostly affected (n = 12; 42.9 %). The narrowest diameters of the distal phalanx cortex and the medulla measured on preoperative X-ray images were 2.8 mm (SD 0.5) and 1.2 mm (SD 0.4), respectively. Seven fusions were done with use of 1 K-wire, 20 with 2 (71.4 %), and 1 with 3 K-wires. The most common K-wire sizes were 1.1-inch (24 K-wires = 48 %), and 0.9 inch (21 K-wires = 42 %) The preoperative VAS score and quick DASH score improved from 6.1 (range: 0–9) and 25.8 (range: 2–38) to 0.4 (range: 0–2) and 3.4 (range: 0–10.2), respectively. 25 (89.3 %) out of 28 fingers achieved bony union in an average of 96.1 days (range: 58–114) with three non-union.Conclusion Arthrodesis of small DIPJs with K-wire fixation has a high success rate. Therefore, we suggest K-wire fixation as an acceptable alternative for patients with a small phalanx which may be at risk of mismatch with bigger implants. However, concerns remain in terms of fusion delay with K-wire only fixation.
Keywords: Distal interphalangeal joint arthrodesis; small distal interphalangeal joints; K-wire fixation